Selected issues of threat management in cyberspace - Barczak, Andrzej; Barczak, Michał (Studia Informatica. System and information technology, 2023)
The paper describes the cyber threat management system. Three essential components of such a system are presented. With reference to such documents as ISO 2700, the NIST Cyber Security Framework, U.S. presidential executive orders, European Union regulations or STIX and TAXIS standards, norms, legal and standards regulations for managing cyber threats are described. The cyber threat management model is presented. Kill Chain and MITRE ATT&CK threat description methods are presented. A toolkit to support various stages of the cyber threat management process is also described.